Mathematics studies at the faculty of nature and mathematics of Vilnius university 1940–1944 - Jasiūnas, Henrikas; Verikaitė, Vitolda (Lietuvos matematikos rinkinys, 2021)
Reorganization of the Polish Vilnius University of Steponas Batoras into Lithuanian Vilnius University in 1940 and the Faculty of Mathematics and Natural Sciences in 1940–1944.